Mistura de lipossomas convencionais e furtivos: estudos farmacocinéticos em camundongos e otimização do processo de encapsulação do antimoniato de meglumina - Ligia Elena de Souza (2013)
Liposomes, being passively targeted to the liver, spleen and bone marrow, which represent the main sites of infection in visceral leishmaniasis (VL), allow the increase of the effectiveness of anti-leishmania drugs, such as pentavalent antimonials, in the treatment of this disease. Previous studies led to development of a meglumine antimoniate (MA) formulation in conventional liposomes made from phosphatidylcholine (DSPC), cholesterol (CHOL) and dicetyl phosphate (DCP), which showed efficacy in the treatment of dogs naturally affected with VL. Furthermore, a more recent study showed that a formulation of MA composed by the mixture of conventional and stealth liposomes was more effective in the elimination of parasites from spleen and bone marrow, when compared to conventional or stealth liposomes administered separately. As a continuation of this work and in order to explain this result, this thesis aimed to: (i) select a lipid composition for stealth liposomes based in its pharmacokinetics properties; (ii) compare the pharmacokinetics and biodistribution of conventional and stealth liposomes when administrated separately or in a mixed form, using MA as a marker; (iii) evaluate the encapsulation of MA in liposomes with different compositions using the FDEL method and a scalable process. Selected stealth liposomes were those formed by DSPC, CHOL, phosphatidylglycerol (DPPG) and pegylated lipid (DSPE-PEG). The pharmacokinetic study of mixed conventional and stealth liposomes showed that conventional liposomes in the presence of stealth ones exhibited an increase of their affinity to the spleen, with no change in their affinity to the liver, which may explain the higher efficacy of the mixed formulation in reducing the spleen parasite load. On the other hand, stealth liposomes showed in the mixture a reduction of their capture by the liver and spleen, when compared to the single formulation. This suggests a greater uptake of these liposomes by other macrophages-rich organs, as the bone marrow, for example. Starting from the DSPC/CHOL/DCP formulation, we found that the exchange of synthetic phospholipid DSPC by natural hydrogenated HSPC, can be carried out without any significant change in the vesicles size and encapsulation efficiency of AM. Nevertheless, the replacement of DCP by DPPG significantly reduced the liposome encapsulation efficiency. The method of producing the liposomes employed only equipment and technology already in use in the pharmaceutical industry. Thus, the feasibility of industrial production of the proposed formulation was established in the present work.